Peningkatan Kemampuan Asertif melalui Terapi Perilaku Kognitif: Menyelami Dampak Positif dalam Pengembangan Komunikasi Personal - Astriani, Defi; Mufidah, Alaiya Choiril; Farantika, Dessy; Prastika, Safina Dwi (Program Studi Psikologi Islam (IAIN) Kediri, 2023)
This research aims to explore the impact of Cognitive Behavior Therapy (CBT) on assertive behavior among Special Education Teachers (SETs). Due to the heavy workload and demands, teachers may experience cognitive disturbances. The study employs a quantitative experimental approach, focusing on a single participant, a 23-year-old SET named PAS, a new teacher in an Inclusive School for Special Needs in Kab Blitar, with low assertive behavior based on interview assessments, observations, graphic tests (BAUM, DAP & HTP), Wartegg, CFIT, and assertiveness scales. Sampling is done purposively. The Assertiveness Inventory serves as the research instrument, administered over eight sessions lasting 60 minutes each. Pre-test and post-test evaluations were conducted to assess changes. The findings indicate an improvement in assertive behavior for the participant, as evidenced by an increase in assertive behavior scores on the Assertiveness Inventory scale. Additionally, a reduction or elimination of negative thoughts and behaviors in the participant was observed. This research is vital for understanding how CBT can effectively enhance assertive behavior, particularly in the context of special education teachers facing significant work-related challenges. The results provide a foundation for developing interventions or programs that can be broadly applied to help educators enhance their assertive communication skills. Moreover, the study sheds light on the positive impacts anticipated from integrating cognitive behavior therapy in the development of assertive behavior.